3.4k views
3 votes
Someone please help me!!!!!!!

Someone please help me!!!!!!!-example-1

2 Answers

4 votes

Answer:

From Step 2 every step is wrong

Explanation:

Ste p 1 : 3a - 5b = 12 - 4(b + a)

Step 2 : 3a - 5b = 12 - 4b - 4a [ Last term instead - 4a she\he wrote + a ]

Step 3 : 7a - 5b = 12 - 4b

Step 4 : 7a = 12 + b


Step 5 : a = (12 + b)/(7)

User ShpielMeister
by
5.4k points
4 votes

Explanation:

In the second step while opening the bracket, instead of 'a', there should be - 4a.

User Joon W K
by
5.7k points